Projecting the Population Level Burden of CKD Progression According to Urine Albumin-to-Creatinine Ratio Categories - Luca De Nicola; Ricardo Correa-Rotter; Juan F. Navarro-González; Albert Power; Michal Nowicki; Istvan Wittmann; Jean-Michel Halimi; Juan Jose Garcia Sanchez; Claudia Cabrera; Salvatore Barone; Timothy Coker; Lise Retat (Kidney International Reports)
Introduction: Urinary albumin-to-creatinine ratio (uACR) is an independent predictor of chronic kidney disease (CKD) progression. However there is limited evidence on the burden of CKD according to uACR categories at the population level. This study estimates future clinical and financial burden of CKD according to uACR categories using the Inside CKD microsimulation. Methods: The Inside CKD model is an individual patient level microsimulation that emulates national populations based on demographic, epidemiological, and economic data. The analysis estimates clinical and economic outcomes over time according to the Kidney Disease: Improving Global Outcomes (KDIGO) uACR categories (A1–A3) at a population level for 31 countries and regions. Results: CKD populations (diagnosed and undiagnosed individuals, stages G3–G5) were projected to be predominantly within uACR categories A1 and A2 in 2022. Projected cumulative incidence of CKD stage transitions (disease progression) and cardio-renal complications (heart failure, myocardial infarction, stroke, and all-cause mortality) occurred mostly in uACR categories A1 and A2 between 2022 and 2027. Patients in uACR categories A1 and A2, who represent the largest proportion of patients with CKD, were projected to incur most of the health care costs associated with CKD management and cardio-renal complications for the diagnosed population (prevalence 2027). Conclusion: This study highlights the disproportionate population-level clinical and economic burden associated with individuals within KDIGO uACR categories A1 and A2, who represent most of the CKD population. This awareness will help health care decision makers to appropriately allocate resources and interventions to the CKD population, including those with mild to moderately increased albuminuria, to reduce clinical and economic burden associated with CKD.